TrwC-Mediated Site-Specific Recombination Is Controlled by Host Factors Altering Local DNA Topology - César, Carolina Elvira (American Society for Microbiology (ASM), 2007)
R388 conjugative relaxase TrwC acts as a site-specific recombinase, promoting recombination between two cognate oriTs on double-stranded DNA substrates. The relaxosome component TrwA is also required for efficient recombination. In this work we present data on the in vivo control of this reaction by host proteins that affect local DNA topology. In the absence of TrwA, binding of integration host factor (IHF) to the oriT keeps the recombination levels low, probably by keeping the relaxosome complex, formed at recombination locus 1, in a “closed” conformation. In an IHF-deficient (IHF(−)) background, the formation of a transcript elongation complex at this locus still hampers recombination. A mutation abating the promoter sequence at locus 1, or repression of transcription by exposure to rifampin, lifts the inhibition imposed on recombination in an IHF(−) background. We also observe an increase in conjugation efficiency under these conditions. Relieving the inhibition imposed by these host factors allows efficient levels of recombination between short oriT loci in the absence of TrwA. The presence of TrwA counteracts these inhibitory effects. TrwA would then activate both recombination and conjugation by switching the conformation of the relaxosome to an “open” form that exposes single-stranded DNA at the nic site, promoting the initial TrwC nicking reaction.